Shear displacement gradient in X‐ray Bragg coherent diffractive imaging. (5th April 2022) - Gorobtsov, Oleg; Singer, Andrej
Abstract : Experimental data are used to extract additional information on external stresses and surface dislocations through the perpendicular component of the atomic displacement gradient retrieved with Bragg coherent diffractive imaging. Abstract : Bragg coherent X‐ray diffractive imaging is a cutting‐edge method for recovering three‐dimensional crystal structure with nanoscale resolution. Phase retrieval provides an atomic displacement parallel to the Bragg peak reciprocal lattice vector. The derivative of the displacement along the same vector provides the normal strain field, which typically serves as a proxy for any structural changes. In this communication it is found that the other component of the displacement gradient, perpendicular to the reciprocal lattice vector, provides additional information from the experimental data collected from nanocrystals with mobile dislocations. Demonstration on published experimental data show how the perpendicular component of the displacement gradient adds to existing analysis, enabling an estimate for the external stresses, pinpointing the location of surface dislocations, and predicting the dislocation motion in in situ experiments.